60 years in the making [videorecording (DVD)] : the story of the Spokane Civic Theatre. - Sondericker, Philip; Treadway, Patrick (Spokane Civic Theatre, 2006)
Features include never-before-seen photos from some of the earliest Civic productions, rare film/videos hidden for years, Civic memorabilia from every decade since the 40's, interviews with Civic leaders. . . past and present, and the complete live telecast from Spokane Civic Theatre's grand opening in 1967.